Jurisdição, processo judicial eletrônico e inteligência artificial : qualificação da tutela jurisdicional pela tecnologia - Costa, Augusto Pereira (2021)
This essay explores the search for efficiency in the jurisdictional activity through technology. The proposal is to analyze the evolution of the movement of virtualization of the judicial procedure, which includes the electionic judicial process Project, as well as the prospects for venturing through the permeation of new technologies such as artificial intelligence in the jurisdiction context. With that in mind, the study was divided into two parts. The general objective of the first part is the description and critical assessment of the way in which the virtualization of the judicial process was projected and the comparison of the prospected and achieved impacts, essentially demonstrating the flaws and inconsistencies in the electronic judicial process model. The second part will seek to contemplate the theme of artificial intelligence applied to the judicial process, its relevance, risks and permeation limits. Each part will be divided into two chapters, which will be finalized with considerations on the topics covered. The first chapter will cover the technological development and its repercussions in the judicial process, passing through topics such as the electronic practice of procedural acts, the virtualization of the judicial process and the model of electronic judicial process in critical analysis. The second chapter will deal with the positive impact of the virtualization of the judicial process, and also the negative impact of the electronic judicial process model, which restricted the exploration of the virtual environment, proposing to rethink it in order to allow a structure (or system design) that is more appropriate. The third chapter will introduce the theme of artificial intelligence, begining with considerations about the human being in the technocentric society and the technological revolution with intelligent machines, as well as outlining relevant aspects such as machine learning, its potentialities, risks, the ability of the machine to play a leading role on decision-making, as well as the importance of ethical regulation for the use and development of technology with an anthropocentric north. The fourth chapter is intended to explore the possibility of permeation of artificial intelligence in the jurisdictional activity, starting with the analysis of the Brazilian regulatory context, the potential permeation levels up to the extreme that is the “robot-judge”, and then proposing limitations that allow the efficient use of technology in the qualification of jurisdictional protection, without sacrifices to the constitutional process model, and, in the end, highlighting the inevitable change in the jurisdictional activity.